2006
DOI: 10.1021/jo061072x
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of 2-Amino-4-phosphonobutanoic Acids by Electrophilic Substitution and Tin−Peterson Olefination of Bis-lactim Ethers Derived fromcyclo-[l-AP4-d-Val]

Abstract: Electrophilic substitutions on lithiated Schöllkopf's bis-lactim ethers derived from cyclo-[L-AP4-D-Val] take place regio- and stereoselectively at the alpha-position of the phosphonate ester. Subsequent olefination of alpha-silyl-, alpha-phosphoryl-, and alpha-stannyl-stabilized phosphonate carbanions give rise exclusively to vinylphosphonates. Both processes allow a direct and stereoselective access to a variety of 4-substituted and 3,4-disubstituted 2-amino-4-phosphonobutanoic acids (AP4 derivatives) in ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Although this feature is a significant drawback to the use of C α -lithiation-electrophilic quench methodology for accessing optically pure Ccentered chiral organophosphorus compounds, the feasibility of diastereo-and enantioselective C α -deprotonations has been demonstrated in a number of cases. Ruiz, Ojea, and coworkers [15] used Schöllkopf's bis-lactim ether derived from l-2-amino-4-phosphonobutanoic acid and d-valine as chiral inductor in the lithiation of phosphonate 32 with LDA. The reaction of the anion 33 formed with a range of electrophiles afforded derivatives 34 containing new carbon-carbon and carbon-heteroatom bonds in good yields.…”
Section: Pc 1 LI Species Via C -Lithiation Of P(iii) Compoundsmentioning
confidence: 99%
“…Although this feature is a significant drawback to the use of C α -lithiation-electrophilic quench methodology for accessing optically pure Ccentered chiral organophosphorus compounds, the feasibility of diastereo-and enantioselective C α -deprotonations has been demonstrated in a number of cases. Ruiz, Ojea, and coworkers [15] used Schöllkopf's bis-lactim ether derived from l-2-amino-4-phosphonobutanoic acid and d-valine as chiral inductor in the lithiation of phosphonate 32 with LDA. The reaction of the anion 33 formed with a range of electrophiles afforded derivatives 34 containing new carbon-carbon and carbon-heteroatom bonds in good yields.…”
Section: Pc 1 LI Species Via C -Lithiation Of P(iii) Compoundsmentioning
confidence: 99%
“…In the same study [34], the (2S,5R)-57 analogue of cyclo-[(S)-AP4-(R)-Val] demonstrated regioselectivity and moderate asymmetric induction during 2'-substitution with a wide range of electrophilic reagents (e.g. a/ MeI, b/ HCO 2 Et, c/ Et 2 CO 3 , d/ N-fluorobenzenesulfonimide (NFSi), e/ Ph 3 SnCl and f/ Et 2 PO 3 Cl) under LDA/THF/-78 o C conditions (Scheme 8b), although some racemisation at C-2 was noted during similar azidation and silylation procedures.…”
Section: Asymmetric Methodologiesmentioning
confidence: 78%
“…The putative chelate intermediate (S-51 case shown), directing the diastereoselectivity of addition, was supported by the decrease in asymmetric induction observed on addition of the high dielectric HMPA, and the Group I ion chelator 18-crown-6, both serving to solvate the K + cation and disrupting the coordination network involving nitrogen and phosphoryl oxygen electron pairs. Chiral aminocarboxylate surrogates used in such approaches have also included the lithiated Schöllkopf's bislactim ethers R-52 and S-52 [32][33][34] (Fig. 2), derived from the corresponding valine isomers, Belokon's Ni(II)-complex with the glycine Schiff base derived from (S)-o-[(Nbenzylprolyl)amino]benzophenone (53) [35], lithiated Seebach's 1,3-imidazolidin-4-ones (2R,1'S)-54 and (2S,1'S)-54 [36,37], and oxazinone 55 [38].…”
Section: Asymmetric Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations